(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2020)
Formoterol Fumarate and Glycopyrrolate Dry powder inhaler is combined aerosol dosage form. The label claim of this combined dosage form is 25 mcg of Glycopyrrolate and 6 mcg of Formoterol Fumarate per respicap. It is prescribed for treatment of Asthma and COPD. Formoterol Fumarate is anti asthmatic drug (Bronchodilator) and Glycopyrrolate is quaternary ammonium compounds which is Anticholinergic Drug. A bronchodilator is a substance that dilates the bronchi and bronchioles, decreasing resistance in the respiratory airway and increasing airflow to the lungs while Glycopyrrolate blocks muscarinic receptors thus inhibiting cholinergic transmission. Glycopyrrolate is also known as Glycopyrronium Bromide, an Anticholinergic agent. It is used to inhibit salivation and excessive secretions of the respiratory tract preoperatively; reversal of neuromuscular blockade; control of upper airway secretions; and part of treatment for peptic ulcer. The present study aimed to Validate HPLC method for determination of Deposition of emitted dose of Formoterol Fumarate and Glycopyrrolate Analytes. This study covers Precision, Linearity, Accuracy, Robustness, Ruggedness, stability of analytical solution and Specificity. The chromatographic method uses a reversed phase column Purosphere star RP 18e (125 mm × 4.6 mm x 5 μm). The mobile phase was prepared by mixing Buffer : Acetonitrile : Methanol (68 : 24 : 8 %v/v/v) at flow rate 1.0 ml per min with UV and PDA detector 215 nm, column oven adjusted to 25° C with injection volume 100 μL. The method showed a successful application for determination of Formoterol Fumarate and Glycopyrrolate in Dry powder inhaler pharmaceutical formulation.